EVALUASI UJI HEDONIK KOPI ROBUSTA LAWU DAN EXCELSA SELONDO SEBAGAI PENENTU TARGET PASAR PENJUALAN KOPI DI KABUPATEN NGAWI - Sholihah, Elis Rahmawati Mar’atus; Mangesti, Getta Hayyuning; Atmojo, Titin Andriyani (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
The purpose of this study is to evaluate the results of the hedonic testing on Robusta Lawu and Excelsa Selondo coffee as a strategy to determine the target market for coffee sales in Ngawi Regency. The research method used in this study is the hedonic test, where the preference test aims to measure the quality of coffee through the five senses (preference, color, aftertaste, flavor, and aroma) as a basis for determining the coffee market share in Ngawi Regency. This hedonic testing was conducted on 50 untrained panelists and 8 semi-trained panelists in Ngawi Regency. The results indicate that the majority of panelists gave positive evaluations to Excelsa Selondo coffee, known for its unique fruity flavor. Meanwhile, Robusta Lawu coffee also received similar positive feedback due to its bitter taste and strong aroma, which are characteristic of robusta coffee. These findings suggest that the target market for Excelsa Selondo coffee tends to be male consumers due to its unique flavor, while Robusta Lawu coffee is more favored for its bitterness. This research provides practical contributions to coffee producers as a basis for planning marketing strategies and determining company marketing policies based on consumer preferences.